FLUCTUATION IN CALCIUM LEVELS IN THE EXOSKELETON, MUSCLE AND HAEMOLYM’PH OF PENAEUS INDICUS, CULTIVATED IN A BRACKI8HWATER POND - Rao, P Vedavyasa; Diwan, A D; Kakati, V S (Indian Journal of Fisheries, 2011)
The calcium content in the exoskeleton of Penaeus indicus cultivated in a brackishwaterpond was found between 4 and 15%, which was low compared to other crustaceans. The haemolymph calcium was observed always at a higher level than the calcium in the pond water. Calcium content of pond water and haemolymph showed a direct relationship wiith the salinity. Relatively high levels of calcium in muscle and low levels in exoskeleton were observed in June, the probable reasons for this abrupt fall in the values are discussed.